Pengaruh Pelatihan dan Kompetensi Terhadap Kinerja Karyawan pada PT. Mandiri Pratama Intilogam Cikarang - Dewi Ratnasari; Anwar Musadad (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study was to determine the correlation of training and competence variables, to determine the partial effect of training variables on employee performance at PT. Mandiri Pratama Intilogam Cikarang. To determine the effect of partial competence on the performance of employees of PT. Mandiri Pratama Intilogam Cikarang. The research method used is descriptive and verification with a quantitative approach. The sample used in this study was 155 people. The sampling technique used is non-probability sampling with propotionate stratified sampling technique. The data analysis technique used is path analysis with partial and simultaneous hypothesis testing. The results of this study are that there is a significant correlation between training and competence and has a strong value of 0.769. There is a positive and significant influence of the training variable on the performance of 0.500 or 50%. There is a positive and significant influence between the competence variables on performance of 0.260 or 26%. Together, the competence and training variables affect employee performance by 75.8% while the remaining 24.2% is explained by other factors not examined in this study.